When Microvasculature Rules: microvascular assessment in invasive coronary angiogram - hassan, Hossameldin; Islam, Mohamed; Sharma, Vinoda (JOURNAL OF ADVANCES IN BIOLOGY, 2023)
Patients with symptoms of ischaemia without obstructive coronary artery disease present a diagnostic and therapeutic challenge. Microvascular angina (MVA) was called before syndrome X. Invasive coronary angiography used commonly to assess those patients. This article provides a common pathway to diagnose MVA using different invasive and non-invasive tests. In addition, it provides insights for treatment and management of patients in this common clinical scenario.